Synthesis and antimycotic activity of new derivatives of imidazo[1,2-a]pyrimidines - Dmitriy Yu. Vandyshev; Daria A. Mangusheva; Khidmet S. Shikhaliev; Kirill A. Scherbakov; Oleg N. Burov; Alexander D. Zagrebaev; Tatiana N. Khmelevskaya; Alexey S. Trenin; Fedor I. Zubkov (Beilstein Journal of Organic Chemistry)
The heterocyclic core of imidazo[1,2-a]pyrimidine was formed in satisfactory yields as a result of the interaction of the readily available 2-aminoimidazole with N-substituted maleimides or N-arylitaconimides. The mechanism of the studied processes was postulated basing on experimental data, HPLC–MS analysis of reaction mixtures, and quantum chemical calculations. Molecular docking results of the obtained imidazo[1,2-a]pyrimidines, when compared with voriconazole, a drug already in clinical use, suggest that they may possess antifungal activity against Candida albicans.